1984
DOI: 10.1016/s0022-5347(17)49943-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of Recurrent Urinary Stress Incontinence by the Marshall-Marchetti-Krantz Vesicourethropexy

Abstract: We studied 114 women who underwent the Marshall-Marchetti-Krantz vesicourethropexy as a secondary procedure for recurrent stress incontinence. Of 99 patients for whom data were available the first operation consisted of vaginal procedures only in 57 (group 1) and suprapubic procedures somewhat related to our method of vesicourethropexy in 42 (group 2). The success rate for group 1 was 80 per cent, while it was 90 per cent for group 2. Cured and improved rates were similar (95 to 96 per cent, respectively). Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…Lack of influence of parity, prior hysterectomy or previous anti-incontinence procedures on the outcome is also in accordance with other authors’ observations [6, 13, 18]. Weak correlation with the age of operated patients may bring the conclusion of shorter duration of continence achieved in women of 60 years of age or older.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lack of influence of parity, prior hysterectomy or previous anti-incontinence procedures on the outcome is also in accordance with other authors’ observations [6, 13, 18]. Weak correlation with the age of operated patients may bring the conclusion of shorter duration of continence achieved in women of 60 years of age or older.…”
Section: Discussionsupporting
confidence: 90%
“…75–97%, although most series revealed more favorable long-term results (70–85%) after 5 years [17, 18, 19]. Nevertheless, two similar series of continence rates of 57 and 67% after 5 years have been published recently which is comparable to our results [6, 13].…”
Section: Discussionsupporting
confidence: 87%
“…In their review of the Marshall‐Marchetti‐Krantz operation, Mainprise and Drutz 14 found the incidence of voiding disorders to be 3.6%, but other authors have reported the incidence to be 24% 63 . Voiding difficulty occurs in 16%‐25% of women after colposuspension 15,64–66 and may persist for ten years or more in one‐fifth of women 4 , and in 2%‐15% of women after endoscopic bladder suspension 12,67–68 .…”
Section: Short Term Complicationsmentioning
confidence: 99%
“…Cette complication est inhérente à la chirurgie de l'IUE et du prolapsus. Elle est rapportée par Parnell et al (168) dans 27 % des cas après une colposuspension de MMK et par Kelly et al (169) dans 41 % des cas après une colposuspension de Peyrera. Dans la majorité des cas, il s'agit d'une rétention de nature transitoire, qui persiste une à deux semaines.…”
Section: Rétention Urinaire Transitoire Postopératoireunclassified